2020
DOI: 10.1038/s41593-019-0564-3
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing in schizophrenia-affected parent–offspring trios reveals risk conferred by protein-coding de novo mutations

Abstract: Competing Interests B.M.N. is on the Scientific Advisory Board at Deep Genomics and Camp4 Therapeutics Corporation, and on the Biogen Genomics Advisory Panel. M.F. is an employee of Verily Life Sciences. Accession codes Data included in this manuscript have been deposited in the database of Genotypes and Phenotypes (dbGaP) under accession number phs001196.v1. Data collection and analysis were not performed blind to the conditions of the experiments. Data availability Data included in this manuscript have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
130
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 50 publications
4
130
0
Order By: Relevance
“…In one patient with COS, we identified a heterozygous missense VUS in SHANK2 (Table 1, Table S2, available online), which codes for a postsynaptic density protein highly expressed in glutamatergic synapses [Peykov et al, 2015]. SHANK2 missense variants have been linked to schizophrenia in case-control and family studies [Homann et al, 2016], but was not identified as a schizophrenia risk gene in a recent, large trio ES study [Howrigan et al, 2020]. The father was unavailable for testing, so we were unable to conclude if it was de novo or paternally inherited, making it more difficult to conclude pathogenicity.…”
Section: Genetic Test Resultsmentioning
confidence: 99%
“…In one patient with COS, we identified a heterozygous missense VUS in SHANK2 (Table 1, Table S2, available online), which codes for a postsynaptic density protein highly expressed in glutamatergic synapses [Peykov et al, 2015]. SHANK2 missense variants have been linked to schizophrenia in case-control and family studies [Homann et al, 2016], but was not identified as a schizophrenia risk gene in a recent, large trio ES study [Howrigan et al, 2020]. The father was unavailable for testing, so we were unable to conclude if it was de novo or paternally inherited, making it more difficult to conclude pathogenicity.…”
Section: Genetic Test Resultsmentioning
confidence: 99%
“…Common risk alleles collectively contribute to around a third of the genetic liability 2,3 , and at least 8 rare copy number variants have been identified as risk factors 4,5 . Exome-sequencing studies have also shown a contribution to risk from ultra-rare protein-coding variants; the de novo mutation rate is modestly elevated above the expected population rate, and there is an excess of ultra-rare damaging coding variants (frequency < 0.0001 in population) in genes with evidence for strong selective constraint against protein-truncating variants (PTVs) [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Liability to disease through common variants (allele frequency ≥ 1%) ranges from 10-25% for psychiatric disorders including major depressive disorder (MDD) (1)(2)(3) and schizophrenia (1,4). Rare variants have likewise been shown to confer disease risk, particularly in neurodevelopmental and psychotic (5,6) domains. While loci containing both types of variants have been associated with neuropsychiatric phenotypes, two major hurdles have prevented use of this knowledge to better understand disease mechanisms: 1) a large volume of GWAS associations and rare variant discoveries to test for functionality/causality; and 2) the lack of means to predict a variant's functional consequences.…”
Section: Introductionmentioning
confidence: 99%